{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

# H9Sol - ECE 3100 Homework#9 Solutions 1 Fall 2009 Since the...

This preview shows page 1. Sign up to view the full content.

This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: ECE 3100 Homework #9 Solutions 1. Fall 2009 Since the covariance remains unchanged when a constant is added to a random variable, we can assume that X and Y have zero mean. Then cov(X + Y, X − Y ) = E [(X + Y )(X − Y )] = E [X 2 − Y 2 ] = E [X 2 ] − E [Y 2 ] = Var(X ) − Var(Y ) = 0. 2. Let Z = |X − Y |, we will ﬁrst compute the CDF of Z . P[Z ≤ z ] = P[|X − Y | ≤ z ] = P[−z ≤ X − Y ≤ z ] = P[Y − z ≤ X ≤ z + Y ] Since X and Y are independent, the last probability can be computed as ￿∞ P[Y − z ≤ X ≤ z + Y ] = fY (y )P[y − z ≤ X ≤ z + y |Y = y ]dy ￿0 ∞ = λe−λy P[y − z ≤ X ≤ z + y ]dy 0 4. Denote by Ni , i = 1, ..., 4, the number of defective transistors in the ith core, then each Ni is a Poisson RV with mean λ moreover the 4 RVs are independent. We are interested in determining the PMF of N = N1 + N2 + N3 + N4 . Consider ﬁrst the RV M1 = N1 + N2 , we have n ￿ P[M1 = n] = P[N1 + N2 = n] = P[N1 = k, N2 = n − k ] k=0 Since N1 and N2 are independent we deduce the following P[M1 = n] = n ￿ k=0 P[N1 = k ]P[N2 = n − k ] n ￿ λk λn−k k ! (n − k )! = e−2λ =e Notice that P[y − z ≤ X ≤ z + y ] = P[X ≤ z + y ] − P[X < y − z ], at this point two cases can be distinguished. Case 1: If y ≤ z , we have P[X < y − z ] = 0 (because X takes only positive values). Hence, using the formula for the CDF of an exponential RV, we obtain P[y − z ≤ X ≤ z + y ] = P[X ≤ z + y ] = 1 − e−λ(z +y) . Case 2: If y > z , using again the formula for the CDF of an exponential RV, we obtain P[y − z ≤ X ≤ z + y ] = 1 − e −λ(z +y ) λn n 2 n! n −2λ (2λ) =e , n! ￿n n! n= k n−k (here applied with a = b = 1). It follows where we have used the binomial theorem (a + b) k=0 k!(n−k)! a b then that M1 is a Poisson RV with mean 2λ, similarly M2 = N3 + N4 will be a Poisson RV with mean 2λ. Notice that M1 depends only on N1 and N2 , while M2 is a function of N3 and N4 , however the RVs Ni are independent of each other, hence M1 and M2 are independent RVs. We conclude therefore that N = M1 + M2 is a Poisson RV with mean 4λ. = e−2λ 1 5. (a) Let Ti , i = 1, ..., n, be independent exponential RVs with respective means µi . Consider T = min(T1 , ..., Tn ), we are interested in determining the PDF of T . Using the independence of the random variables T1 , ..., Tn , the complementary CDF of T is given by k=0 n n￿ −2λ λ n! k=0 n! k !(n − k )! − (1 − e −λ(y −z ) )=e −λ(y −z ) −e −λ(z +y ) . Going back to P[Z ≤ z ] we have ￿z ￿∞ P[Z ≤ z ] = λe−λy P[y − z ≤ X ≤ z + y ]dy + λe−λy P[y − z ≤ X ≤ z + y ]dy 0 z ￿z ￿∞ = λe−λy (1 − e−λ(z +y) )dy + λe−λy (e−λ(y−z ) − e−λ(z +y) )dy z ￿0 z ￿z ￿∞ = λe−λy dy − e−λz λe−2λy dy + (eλz − e−λz ) λe−2λy dy 0 z ￿ ∞0 ￿∞ = 1 − e−λz − e−λz λe−2λy dy + eλz λe−2λy dy 1 1 = 1 − e−λz − e−λz + eλz e−2λz 2 2 = 1 − e−λz . 0 z P[T > t] = P[min(T1 , ..., Tn ) > t] = P[T1 > t, ..., Tn > t] = P[T1 > t] × ... × P[Tn > t] = e−µ1 t × ... × e−µn t 1 Hence T is an exponential RV with mean µ , where µ = 5. (b) Let the random variable K indicate which of the n components caused the jPhone to fail, i.e., From part (a) we know that Yk = min(T1 , ..., Tk−1 , Tk+1 , ..., Tn ) is an exponential RV with mean ν1 , where νk = k µ − µk . Notice now that Yk is a function of (T1 , ..., Tk−1 , Tk+1 , ..., Tn ) which are independent of Tk , hence Tk and Yk are independent. Consequently, the following sequence of equalities follows P[K = k ] = P[Tk ≤ Yk ] ￿∞ = fTk (t)P[Yk ≥ t|Tk = t]dt ￿0 ∞ = µk e−µk t P[Yk ≥ t]dt ￿0 ∞ = µk e−µk t e−νk t dt ￿0 ∞ = µk e−(µk +νk )t dt = µk µk = ￿n . µk + νk i=1 µi 2 0 = e−(µ1 +...+µn )t . ￿n i=1 µi . P[K = k ] = P[Tk = T ] = P[Tk ≤ min(T1 , ..., Tk−1 , Tk+1 , ..., Tn )]. From the last equality we see that Z = |X − Y | is an exponential random variable with mean given by fZ (z ) = λe−λz for z > 0 and fZ (z ) = 0 otherwise. 1 λ and hence with PDF 3. (a) Let Y = g (X ) = sin(X ). Then for X ∈ [0, 2π ], Y takes values in the interval [−1, 1], and is not uniformly distributed over [0,1]. The Penn student is therefore incorrect. 3. (b) Let g (x) = x 2π . Then Y = g (X ) = X 2π , and Y ∈ [0, 1]. Thus fY (y ) = 0 for y ∈ [0, 1]. For y ∈ [0, 1], we have / 1 = y, 2π FY (y ) = P(g (X ) ≤ y ) = P(X/2π ≤ y ) = P(X ≤ 2π y ) = 2π y · and fY (y ) = d dy FY (y ) = 1. Thus Y is uniform over [0, 1]. 1 6. R1 and R2 have standard deviation 100Ω. Thus Var(R1 ) = Var(R2 ) = 1002 Ω2 = 0.01(kΩ)2 . We thus have R1 ∼ N (1, 0.01) and R1 ∼ N (1, 0.01) with R1 and R2 independent. We wish to compute ￿ ￿￿ ￿ ￿ ￿ ￿ ￿ ￿ R2 1 ￿ 0.05 R2 0.95 R2 1.05 ￿ P￿ =P < +P > ￿ R1 + R2 − 2 ￿ > 2 R1 + R2 2 R1 + R2 2 = P(2R2 < 0.95R1 + 0.95R2 ) + P(2R2 > 1.05R1 + 1.05R2 ) = P(0.95R1 − 1.05R2 > 0) + P(0.95R2 − 1.05R1 > 0). 2 2 Let Z1 = 0.95R1 − 1.05R2 and Z2 = 0.95R2 − 1.05R1 . Using the fact that X ∼ N (µ1 , σ1 ), Y ∼ N (µ2 , σ2 ), 2 2 X and Y independent, implies aX + bY ∼ N (aµ1 + bµ2 , a2 σ1 + b2 σ2 ), we have Z1 ∼ N (−0.1, 0.02005) and Z2 ∼ N (−0.1, 0.02005). Since Z1 and Z2 have the same distribution, the required probability becomes P(Z1 > 0) + P(Z2 > 0) = 2P(Z1 > 0). We can compute P(Z1 > 0) either numerically by integrating the Gaussian PDF or from Normal distribution tables. In both cases, we obtain P(Z1 > 0) = 0.223, and thus ￿ ￿￿ ￿ ￿ R2 1 ￿ 0.05 ￿ P￿ = 2P(Z1 > 0) = 0.446. ￿ R1 + R2 − 2 ￿ > 2 3 ...
View Full Document

{[ snackBarMessage ]}

Ask a homework question - tutors are online